2012
DOI: 10.1007/s13181-012-0233-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course of Bark Scorpion Envenomation Managed Without Antivenom

Abstract: Bark scorpion envenomation is potentially life threatening in children and traditionally treated with antivenom (AV). We sought to describe the clinical course, management, complications and outcome of children with severe scorpion envenomation treated with supportive care during a period when AV was unavailable. A retrospective chart review was performed, all children presenting to a referral hospital between September 1, 2004 and July 31, 2006 with severe scorpion envenomation not receiving AV, were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…Children under 10 years of age had the highest frequencies of major effects, as well as vomiting, a finding which has been reported previously [25]. This age group also had the highest frequency of hospitalization and ICU admission.…”
Section: Discussionsupporting
confidence: 80%
“…Children under 10 years of age had the highest frequencies of major effects, as well as vomiting, a finding which has been reported previously [25]. This age group also had the highest frequency of hospitalization and ICU admission.…”
Section: Discussionsupporting
confidence: 80%
“…Children in this group were older and only 3 % had respiratory distress. The mean ED LOS of 261 min in this group, while similar to the other treatment groups in this study, differs greatly from the LOS of 28.7 h that was reported in a previous pediatric scorpion envenomation cohort presenting to PCH when antivenom was unavailable [7]. This comparison highlights the relative mild severity of illness of children in group 1.…”
Section: Discussionsupporting
confidence: 62%
“…Common pharmacologic treatment includes benzodiazepine and opioid administration to control agitation and pain [7,8]. With only supportive care, patients often require admission to the ICU and mechanical ventilation [7].…”
Section: Introductionmentioning
confidence: 99%
“…The classical triad contains myalgia, generalized weakness, and dark colored urine. Conner reported that rhabdomyolysis developed in 20% of cases after scorpion envenomation (10). Levels of CK were seen above 1000 IU/L in patients that developed rhabdomyolysis in the same study.…”
Section: Discussionmentioning
confidence: 59%